Implementing Total Quality Management to Enhance Vocational School Graduates' Competitiveness: A Case Study in West Java - Deddy Hermadi; Endang Komara; Agus Mulyanto; Ahmad Khori (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to evaluate the effectiveness of the implementation of Total Quality Management (TQM) in increasing the competitiveness of Vocational High School (SMK) graduates in West Java. This topic is important because it is a strategic effort to bridge the gap between vocational education and the needs of dynamic industries. This study uses a qualitative approach to deeply understand how industrial internship programs are integrated into the curriculum and their impact on students and the school's relationship with industry. Data was collected through observation, interviews with the vice principal for curriculum, and document analysis. The data source came from SMK Negeri 9 Bandung City and SMK Negeri 1 Cimahi City which were selected using purposive sampling techniques. Data analysis is carried out interactively and continuously through data reduction, data presentation, and conclusions drawn. Case studies in two vocational schools show that the PDCA (Plan, Do, Check, Action) cycle has been implemented systematically. However, challenges still arise in terms of synchronizing the curriculum with industry needs and resource limitations. The findings show a significant increase in the readiness of graduates to enter the world of work. This study concludes that TQM can be an effective framework for improving the quality of vocational education, provided that it is supported by conducive policies and stronger collaboration between schools, industry, and the government.